FAKTOR YANG BERPENGARUH TERHADAP PERATAAN LABA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2009-2012 - Fitri Handayani; Fuad Fuad (Diponegoro Journal of Accounting, 2015)
Investors often focus only on the information return, regardless of the procedure used to generate the income information, it encourages managers to perform on earnings management and lead management to manage earnings in its efforts to create an entity looks good financially. One of the management measures on earnings that can be done is to measure income smoothing (income smoothing). The purpose of this study was to analyze the factors that affect the practice of income smoothing on automotive companies listed on the Stock Exchange in the year 2009-2012. The population of this research is all the financial data of listed companies on the Stock Exchange 2009-2012 period. Sampling method used in this research is purposive sampling method. The sample used in this study are automotive companies listed on the Stock Exchange in 2009-2012. The data  used  are secondary data  from  BEI.  The analysis  technique used  is  multiple linear regression analysis. Based on the research results, profitability, and leverage a negative effect on income smoothing while the size of the company, dividend policy, the auditor's reputation and institutional ownership has no effect on income smoothing. Based Nagelkerke R Square is seen that the magnitude of the coefficient of determination indicated by the value Nagelkerke R Square of 0.396, this means that income smoothing variations can be explained by the independent variable of 39.6%.